Cryptocurrency as an object of accounting and a source of economic benefits - Krupka, Yaroslav; Okrenets, Volodymyr (Herald of Economics, 2020)
Introduction. Cryptocurrency and related activities in Ukraine are not regulated by specialized law. Transactions with currency «crupto» are increasingly used in the accounting practice of domestic enterprises. The correctness of an accounting of such transactions is influence on actuality of the financial statements, the completeness of the taxes payment and the amount of income and profits of enterprises.The main aim is to analyze the peculiarities of the formation and movement of cryptocurrency, its recognition as an object of accounting, justification for further accounting evaluation and impact on performance.Methods. Methods observation, comparison, analogy, grouping and classification, abstraction and specification, analysis and synthesis, tabular and structural-logical methods are used. The information base of the research is the scientific achievements of domestic and foreign scientists and specialists, own experience and observations.Results. The definition of cryptocurrency as an object of accounting and a source of economic benefits is considered. The possibilities and advantages of cryptocurrency using in different spheres of economy are determined and systematized. The role and significance of cryptocurrency with the functions of money are compared. The possibility of classifying cryptocurrency as a certain type of enterprise assets in accordance with IAS and UAS (P(S)BO) is analyzed. The peculiarities of valuation and accounting of cryptocurrency as an intangible asset are substantiated. The problems of taxation of cryptocurrency transactions are identified and certain solutions are proposed until the regulatory settlement of this issue.